Preventing eating disorders among young elite athletes: a randomized controlled trial - Martinsen, M.; Bahr, R.; Borresen, R.; Holme, I.; Pensgaard, A. M.; Sundgot-Borgen, J. (Medicine & Science in Sports & Exercise, 2014)
Purpose: To examine the effect of a 1-yr school-based intervention program to prevent the development of new cases of eating disorders (ED) and symptoms associated with ED among adolescent female and male elite athletes.